(3JjLGf GdeYHhOGJ GdeUQjI ai afhf HdGO GdTGe MJi fgGjI GdCda GdChd bHd GdejdGO (B/s Remainder of title - (3, fhQgGf eMeO eUWaj eMehO s; (3SdjeGf MGeO GdMhjdis; (3YGOd CMeO Rjf GdYGHOjfs; (3fGUQ eMeO ecGhis (2024)
(3JfbSe GdOQGSI Edi CQHYI aUhd(B: (3jJfGhd GdaUd GdChd GdJGL GdMJMhQi ai afhf HdGO GdTGe ai cKjQ ef GdehGbY GdCKQjI ai ShQjG, hJfGhd GdaUd GdKGfi JGL GdBJa (B((3GdJGL GdChRjQi(B) (3ai afhf HdGO GdTGe ef NdGd af GdfMJ hGdfbT ef NdGd GdYOjO ef GdehGbY GdBKQjI(B. (3CeG GdaUd GdKGdK abO JfGhd GdJjLGf GdeUQjI GdBNQi ai afhf HdGO GdTGe(B((3ShQjG(B- (3adSWjf(B). (3ai Mjf JfGhd GdaUd GdQGHY OQGSI JMdjdjI ebGQfI(B: (3abO gOa gPG GdaUd dEYGOI aMU GdCSHGH Ch GdWQb GdJi YQaJ HdGO GdTGe ef NdGdgG GdeYHhOGJ GdeUQjI(B. (3hcPdc GdWQb hGdCSHGH GdJi SeMJ HONhd YOO ef GdeYHhOGJ GdShQjI deUQ, hOQGSI HOGjI XghQge ai GdMjGI GdSjGSjI hGdOHdheGSjI GdeUQjI hYdGbJge HGdeYHhOGJ GdeUQjI(B. (3hjNJJe GdHMK HCge GdfJGFL GdeJQJHI Ydi GdOQGSI(B. (3hLOhd Refi dHdGO GdTGe dJhKjb GdeQGLY GdeSJNOeI ai GdOQGSI(B. (3hbGFeI HGdeQGLY GdYQHjI hGdCLfHjI(B.s
The study is divided into an introduction and four chapters: The first chapter deals with: The Hathoric crown in the art of the Levant, in many Archaeological sites in Syria - The second chapter deals with: The Atef (Crown of Osiris) in the art of the Levant through many archaeological sites in Syria. - The third chapter deals with: Other Egyptian crowns in the arts of the Levant (Syro-Palestine), others. - While the fourth chapter deals with: Comparative analytical study: The proposed chapter managed to reexamine the causes or ways of important and acculturation of some Ancient Egyptian deities into the Syro-Palestinian pantheon, and also the causes or ways of important into the Egyptian pantheon. Studding their appearances at the political and diplomatic level and their acculturation with Egyptian deities. The research concludes with the most important results of the study. And a list of Arabic and foreign references.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B156-175.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3Gdaf GdeUQi GdbOjes; (3WHYGJ GdCNJGe GdCSWhGfjIs -- (3GdfbhT GdShQjI GdadSWjfjIs -- (3af GdfMJ GdShQi GdadSWjfis -- (3GdJGL GdMJMhQis